Prospective study and proposal of an outcome predictive nomogram in a consecutive prospective series of differentiated thyroid cancer based on the new ATA risk categories and TNM - Sapuppo, Giulia; Grasso, Sonia; Di Benedetto, Guenda; Belfiore, Antonino; Pellegriti, Gabriella (Frontiers in Endocrinology, 2023)
Introduction The personalized management of differentiated thyroid cancer (DTC) is currently based on the postoperative TNM staging system and the ATA risk stratification system (RSS), both updated in 2018 and 2015, respectively. Purpose We aimed to evaluate the impact of the last two editions of TNM and ATA RSS in the prediction of persistent/recurrent disease in a large series of DTC patients. Patients and methods Our prospective study included 451 patients undergone thyroidectomy for DTC. We classified the patients according to TNM (both VIII and VII ed.) and stratified them according to the ATA RSS (both 2015 and 2009). We then evaluated the response to the initial therapy after 12-18 months according to the ATA “ongoing” risk stratification, and analyzed the variables associated with persistent/recurrent disease by multivariate analysis. Results The performance of the last two ATA RSSs was not significantly different. By staging patients according to the VIII or VII TNM editions, we found significant differences only in the distribution of patients with structural disease classified in stages III and IV. At multivariate analysis, only T-status and N-status were independently associated with persistent/recurrent disease. Overall, ATA RSSs and TNMs showed low predictive power in terms of persistent/recurrent disease (by Harrell’s test). Conclusions In our series of DTC patients, the new ATA RSS as well as the VIII TNM staging provided no additional benefit compared to the previous editions. Moreover, the VIII TNM staging system may underestimate disease severity in patients with large and numerous lymph node metastases at diagnosis.